2021
DOI: 10.1093/infdis/jiab309
|View full text |Cite
|
Sign up to set email alerts
|

Is SARS-CoV-2 Infection a Risk Factor for Early Pregnancy Loss? ACE2 and TMPRSS2 Coexpression and Persistent Replicative Infection in Primitive Trophoblast

Abstract: Background SARS-CoV-2 infection in term placenta is relatively rare. However, growing evidence suggests that susceptibility of the human placenta to infection may vary by gestational age and pathogen. For several viral infections, susceptibility appears to be greatest during early gestation. Infections of the peri-implantation placenta that result in pre-clinical pregnancy loss would typically go undetected. Little is known about the effects of SARS-CoV-2 on the peri-implantation human placen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Unlike TB derived from term placenta, BAP-generated primitive TB of the early first trimester has diminished levels of 1) interferon-stimulated genes (ISG), such as ISG15 , MX1 , DDX58 ( RIG- 1), 2) interferon induced proteins with tetratricopeptide repeats ( IFIT ) family members, 3) and oligoadenylate synthase-like ( OAS ) family members, all of which augment the innate immune response to viral infection ( 44 , 45 ). Such diminished responses have been linked to a greater risk of vertical transmission of viruses in early gestation including transmission of CMV, HSV, Zika virus and SARS-CoV-2 ( 46 – 50 ). Our RNA-seq analysis revealed that expression of several ISGs were upregulated when VTCN1 expression was repressed ( Figure 3A ).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike TB derived from term placenta, BAP-generated primitive TB of the early first trimester has diminished levels of 1) interferon-stimulated genes (ISG), such as ISG15 , MX1 , DDX58 ( RIG- 1), 2) interferon induced proteins with tetratricopeptide repeats ( IFIT ) family members, 3) and oligoadenylate synthase-like ( OAS ) family members, all of which augment the innate immune response to viral infection ( 44 , 45 ). Such diminished responses have been linked to a greater risk of vertical transmission of viruses in early gestation including transmission of CMV, HSV, Zika virus and SARS-CoV-2 ( 46 – 50 ). Our RNA-seq analysis revealed that expression of several ISGs were upregulated when VTCN1 expression was repressed ( Figure 3A ).…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 vaccination in pregnancy is a severe health concern given the increased maternal mortality and severe disease possible with COVID-19 infection in pregnancy [1,2,66,67]. Evidence of vaccination hesitancy in pregnancy can be observed in the study by Germann et al who conducted a multivariate Poisson regression analysis to estimate vaccination by baseline vaccination hesitancy status.…”
Section: Concept Of Vaccination Hesitancy In Pregnancymentioning
confidence: 99%
“…While TMPRSS2 expression begins later in blastocysts, primarily in the trophectoderm, ACE2 first occurs in embryos early [99]. Strong ACE2/TMPRSS2 co-expression in day 6 peri-implantation embryos indicates susceptibility [100]. Day 5-7 blastocysts containing ACE2/BSG are indicative of SARS-CoV-2 susceptibility.…”
Section: Vulnerability Of Embryos To Sars-cov-2mentioning
confidence: 99%